One-pot synthesis of Mn–Fe bimetallic oxide heterostructures as bifunctional electrodes for efficient overall water splitting. Issue 38 (30th September 2020) - Luo, Juan; Guo, Wan Hui; Zhang, Qing; Wang, Xiao Hu; Shen, Li; Fu, Hong Chuan; Wu, Li Li; Chen, Xiao Hui; Luo, Hong Qun; Li, Nian Bing
Abstract : Benefiting from the synergistic effect and heterogeneous interface, MnFeO-NF-0.8 and MnFeO-NF-0.4 exhibit remarkable electrocatalytic activities for the HER and OER, respectively. Abstract : The design of Earth-abundant and cost-effective electrocatalysts for highly active and stable electrochemical water splitting in practical production is the primary demand. Herein, bimetallic oxides anchored to three-dimensional (3D) porous conductive nickel foam (NF) are constructed using a simple in situ hydrothermal method for efficient overall water splitting. The vertically aligned Mn3 O4 /Fe2 O3 heterojunction nanosheets have synergy between hierarchical metal oxides and heterogeneous interface, and show excellent performance toward the oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) in an alkaline environment. By adjusting the molar ratio of Fe : Mn, the morphology, composition and electronic structure of MnFeO-NF- x composites ( x represents the ratio of Fe : Mn) can be adjusted to exhibit diverse catalytic activities. In particular, MnFeO-NF-0.4 (0.4 indicates the Fe : Mn ratio of 0.4 : 1) and MnFeO-NF-0.8 display outstanding performance with ultralow overpotentials of 157 mV for the OER and 64 mV for the HER to achieve a current density of 10 mA cm −2, respectively. Furthermore, MnFeO-NF-0.4 and MnFeO-NF-0.8 are assembled into a water splitting electrolyzer, which can reach a current density of 10 mA cm −2 with a low voltage of 1.59 V. Interestingly, Mn–M (M = Co, Ni, and Mo) products can be obtained easily by using different metal salts, indicating the universality of the current one-pot hydrothermal method.